Création de la Communauté d’Agglomération Pays Basque : compétences, gouvernance et financement - Pr. Eguzki Urteaga (L'Espace Politique)
After the vote of the 158 municipal councils of the Basque Country concerning the creation of a single Public Establishment of Intercommunal Cooperation (EPCI) for this territory, which resulted in a qualified majority of the municipalities pronouncing themselves in favour of the constitution of a Community of Agglomeration of the Basque Country, the signature of the prefectoral decree establish the creation of this entity, the steering committee in charge of its implementation specifies the competences, governance and taxation of this new institution, which forced the elected representatives to decide between the different options highlighted by the experts and the State services; and this, knowing that this flexible institution is bound to evolve over time. Since 1 January 2017, the ten EPCIs of the Basque Country have merged to provide this territory with a new representative institution which, in two years, has taken on all the competences provided for by the law and has designed and implemented 23 sectoral policies. However, this has not been achieved without difficulties synonymous of a reduction in State allocations and the centralisation of administrations and decision-making.